Use of infrared thermography to evaluate differences in mean body surface temperature and radiant heat loss in growing pigs - J A Loughmiller; M F Spire; S B Hogge; B W James; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
Eighty barrows were used in two experiments to determine the relationship between feed intake or dietary energy concentration and mean body surface temperature (MBST) and mean body surface radiant heat loss (MBSL) as measured using infrared thermographic images. In Exp. 1, feed intake level was varied. As expected, pigs with higher feed intake grew faster. The faster growing pigs had higher MBST and MBSL. In Exp. 2, pigs (initially 130 lb) were allotted to one of four dietary energy levels (1,250 ME/lb, 1,360 ME/lb, 1,475 ME/lb, 1,590 ME/lb). Increasing dietary ME levels increased ADG, G/F, ME intake, MBST, and MBSL. These experiments indicate that infrared thermography can detect MBST and MBSL changes in growing pigs caused by changes in dietary intake or energy level.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Infrared thermography; Dietary energy; Growing pigs